2018
DOI: 10.2174/1389201019666180620112528
|View full text |Cite
|
Sign up to set email alerts
|

Glutamatergic Deficits in Schizophrenia – Biomarkers and Pharmacological Interventions within the Ketamine Model

Abstract: Background: The observation that N-methyl-D-aspartate glutamate receptor (NMDAR) antagonists such as ketamine transiently induce schizophrenia-like positive, negative and cognitive symptoms has led to a paradigm shift from dopaminergic to glutamatergic dysfunction in pharmacological models of schizophrenia. NMDAR hypofunction can explain many schizophrenia symptoms directly due to excitatory-to-inhibitory (E/I) imbalance, but also dopaminergic dysfunction itself. However, so far no new drug targeting the NMDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 111 publications
(187 reference statements)
6
22
0
Order By: Relevance
“…At the same time, convergent evidence shows that the expression of GSK-3β and its related signaling pathways have changed in individuals affected by schizophrenia [34]. In addition, several different atypical antipsychotic drugs have been reported to increase the inhibitory phosphorylation of GSK-3β in brain regions of rats [35][36][37][38]. Furthermore, some other studies have reported a high correlation between Akt gene variants and schizophrenia [39,40].…”
Section: Discussionmentioning
confidence: 97%
“…At the same time, convergent evidence shows that the expression of GSK-3β and its related signaling pathways have changed in individuals affected by schizophrenia [34]. In addition, several different atypical antipsychotic drugs have been reported to increase the inhibitory phosphorylation of GSK-3β in brain regions of rats [35][36][37][38]. Furthermore, some other studies have reported a high correlation between Akt gene variants and schizophrenia [39,40].…”
Section: Discussionmentioning
confidence: 97%
“…An additional advantage presented by animal models is that virtually all experimental practices employed in human studies have homologs for animal experimentation, allowing for direct comparison while simultaneously offering more mechanistic insight. For instance, ketamine, along with another N-methyl-D-aspartate receptor (NMDAR) antagonists, is known to reduce the MMN in humans as well as rodents and non-human primates (Ehrlichman et al, 2008;Gil-Da-Costa et al, 2013;Chen et al, 2015;Haaf et al, 2018;Schuelert et al, 2018). Furthermore, the oddball task applies to a wide variety of experimental assays in animal research.…”
Section: The "Oddball" Paradigmmentioning
confidence: 99%
“…One point to consider in this problem is that NMDAR blockade, a face-valid model of SZ sensory processing features, also reduces MMN in humans and animals (Ehrlichman et al, 2008;Gil-Da-Costa et al, 2013;Haaf et al, 2018;Schuelert et al, 2018). The nature of how NMDAR blockade affects the time-course and oscillatory aspects of auditory MMN has led to the interpretation that DD specifically is NMDAR-dependent (Javitt et al, 1996;Lee et al, 2018).…”
Section: Specific Stimulus Adaptationmentioning
confidence: 99%
“…Deactivation was observed in a number of BOLD rs‐fMRI studies in the subgenual anterior cingulate cortex (SgACC) and the medial orbitofrontal cortex . Considering functional connectivity (seed‐based or global brain connectivity/GBC), generally, an increased pattern of connectivity was observed by most authors (for a review see Maltbie et al and Haaf et al). Shortly, Höflich observed hyperconnectivity between the thalamus and both parietal and temporal cortex; Dandash reported increased FC of the striatum, thalamus, midbrain and PFC; Driesen also observed elevated FC of the thalamus and striatum; and Fleming reported increased FC between the frontal pole, ACC, PCC and insula.…”
Section: Discoordination In Large‐scale Networkmentioning
confidence: 99%